2013
DOI: 10.1021/bi400914c
|View full text |Cite
|
Sign up to set email alerts
|

CD36 Enhances Fatty Acid Uptake by Increasing the Rate of Intracellular Esterification but Not Transport across the Plasma Membrane

Abstract: CD36 is a multifunctional protein that enhances cellular fatty acid (FA) uptake, a key step in energy metabolism, and its dysregulation in multiple tissue sites is central to obesity-linked diabetes, a risk factor for atherosclerosis. Although CD36 has been implicated in FA uptake in a correlative way, the molecular mechanisms are not known. Their elucidation in cells is confounded by receptor-mediated uptake of low-density lipoprotein by CD36 and the competitive and/or contributive effects of other proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 36 publications
2
83
1
1
Order By: Relevance
“…Mice deficient in caveolin-1 are lean and protected from high fat diet induced adiposity (75). Although caveolins might influence FA uptake by modulating CD36 localization to lipid rafts, CD36-independent effects of caveolin on FA uptake can be observed (17, 99). In the intestine caveolin-1 is expressed on enterocyte brush border membranes and the apically absorbed FA appears to be internalized by enterocytes in detergent resistant and caveolin-1 containing vesicles that also contain alkaline phosphatase and CD36.…”
Section: Role Of Cd36-mediated Fa Uptake and Signaling In Absorption mentioning
confidence: 99%
“…Mice deficient in caveolin-1 are lean and protected from high fat diet induced adiposity (75). Although caveolins might influence FA uptake by modulating CD36 localization to lipid rafts, CD36-independent effects of caveolin on FA uptake can be observed (17, 99). In the intestine caveolin-1 is expressed on enterocyte brush border membranes and the apically absorbed FA appears to be internalized by enterocytes in detergent resistant and caveolin-1 containing vesicles that also contain alkaline phosphatase and CD36.…”
Section: Role Of Cd36-mediated Fa Uptake and Signaling In Absorption mentioning
confidence: 99%
“…CD36 is a plasma membrane receptor that binds multiple ligands including fatty acids ( 30,39 ). Recent studies have suggested that CD36 does not directly transport fatty acids across the plasma membrane, but rather through signaling events or direct interaction with enzymes such as acyl-CoA synthetase it enhances fatty acid uptake and promotes TG synthesis ( 40 ). CD36 mRNA levels were reduced by 90% in CETP + cells grown in oleatecontaining media, suggesting that reduced fatty acid uptake may explain the reduced fl ux of fatty acids through the TG biosynthetic pathway.…”
Section: Effect Of Cetp Overexpression On Cholesterol Metabolismmentioning
confidence: 99%
“…However, in the insulin-resistant state, which is a condition often associated with central obesity, adipocyte lipolysis increases regardless of nutritional fluctuations, leading to the release of abundant FFAs into the blood [12]. In the liver, several membrane-bound proteins are responsible for transporting circulating FFAs into hepatocytes, including fatty acid transporter protein (FATP)-2 [15], FATP-5 [16], fatty acid translocase (FAT/CD36) [17][18][19], caveolins [20,21], fatty acid binding proteins (FABP)-1, FABP-4, and FABP-5 [22,23]. Upregulation of several FFA transporters is associated with increased insulin resistance and hepatic steatosis in NAFLD patients [24][25][26][27].…”
Section: Increased Hepatic Fatty Acid Uptakementioning
confidence: 99%